Antarctica-Regional Climate and Surface Mass Budget - Favier, Vincent; Krinner, Gerhard; Amory, Charles; Gallée, Hubert; Beaumet, Julien; Agosta, Cécile (Current climate change reports, 2017)
We review recent literature on atmospheric, surface ocean and sea-ice observations and modeling results in the Antarctic sector and relate the observed climatic trends with the potential changes in the surface mass balance (SMB) of the ice sheet since 1900. Estimates of regional scale SMB distribution and trends remain subject to large uncertainties. Approaches combining and comparing multiple satellite and model-based assessments of ice sheet mass balance aim at reducing these knowledge gaps. During the last decades, significant changes in atmospheric circulation occurred around Antarctica, due to the exceptional positive trend in the Southern Annular Mode and to the climate variability observed in the tropical Pacific at the end of the twentieth century. Even though climate over the East Antarctic Ice-Sheet remained quite stable, a warming and precipitation increase was observed over the West Antarctic Ice-Sheet and over the West Antarctic Peninsula (AP) during the twentieth century. However, the high regional climate variability overwhelms climate changes associated to human drivers of global temperature changes, as reflected by a slight recent decadal cooling trend over the AP. Climate models still fail to accurately reproduce the multi-decadal SMB trends at a regional scale, and progress has to be achieved in reproducing atmospheric circulation changes related to complex ocean/ice/atmosphere interactions. Complex processes are also still insufficiently considered, such as (1) specific polar atmospheric processes (clouds, drifting snow, and stable boundary layer physics), (2) surface firn physics involved in the surface drag variations, or in firn air depletion and albedo feedbacks. Finally, progress in reducing the uncertainties relative to projections of the future SMB of Antarctica will largely depend on climate model capability to correctly consider teleconnections with low and mid-latitudes, and on the ability to correct them for biases, taking into account the coupling between ocean, ice, and atmosphere in high southern latitudes.